Integrated morphological, genetic and path coefficient analysis of yield-related traits in high-yielding linseed (Linum usitatissimum L.) mutants: MORPHOLOGICAL, GENETIC AND PATH COEFFICIENT ANALYSIS OF YIELD TRAITS IN LINSEED - ANIRUDDHA S DESHPANDE; S N MALODE (Journal of Oilseeds Research, 2026)
The present study aimed to characterize high-yielding mutants of Linum usitatissimum var. PKV NL-260 induced through EMS, SA, and gamma-ray mutagenesis to assess the induced genetic variability and interrelationships among yield-contributing traits. Five high-yielding mutants were isolated and evaluated across three successive generations (M2 , M3 , and M4 ) to determine the stability of the induced characters. All mutants exhibited notable improvements over the control in traits such as the number of primary branches, the number of capsules/plant, seed test weight, and seed yield/plant. Genetic variability analysis revealed high values of the genotypic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), heritability, and genetic advance for capsules/plant, seeds/capsule, seed test weight, and seed yield/plant, indicating substantial scope for selection. Correlation analysis showed significant positive associations of plant height, number of primary branches, capsules/plant, seeds/capsule, and seed test weight with seed yield/plant. Furthermore, path coefficient analysis demonstrated that these traits exerted significant positive direct effects on seed yield/plant, highlighting their importance in yield improvement strategies.